Cognition, Memory Types, Functions, and Language Learning Strategies - Hamada, Hacene (University of Eloued جامعة الوادي, 2016)
What does the mind consist of and how does it function? Does the mind lead our learning process towards perfection? Cognitive psychologists attempt to structure the organisation of our mind into cognitive levels, mental processes, and memory types purposefully, not for the sake of distinction but for the sake of comprehensiveness, in order to help us understand how our mind functions. Thus, this paper attempts to answer the above stated questions and provide an overview of the major concerns of information processing in cognitive theory in order to demonstrate that short term, long term, dynamic, active, working memory and episodic, semantic tacit memory types are not distinctive parts but correlative interdependent mental processes that come into play when we are performing our daily learning strategies. Remembering our ‗first day at school‘, recalling when one learns the meaning of ‗honesty‘ or how one ‗takes notes in a lecture‘ without paying attention to spelling and handwriting are all examples of complex mental processes and tasks that are generated by memory types. Exploiting these mental processes and memory types in pedagogical settings provides teachers with strategy based instruction techniques and learners with language learning strategies.
THE SECOND NATIONAL CONFERENCE ON LANGUAGE, MIND AND LEARNER'S COGNITIVE CAPACITIES March, 7th/8th 2016 University of Eloued
Keywords: Cognition, Memory Types, Functions, Language Learning Strategies